Metabolites in stored platelets associated with platelet recoveries and survivals. Issue 8 (9th May 2016) - Zimring, James C.; Slichter, Sherrill; Odem‐Davis, Katherine; Felcyn, Jacob R.; Kapp, Linda M.; Bell, Lauren N.; Gunst, P. Ross; Corson, Jill; Jones, Mary Kay; Pellham, Esther; Bailey, S. Lawrence; Fu, Xiaoyun
Abstract : BACKGROUND: Transfusion of platelets (PLTs) is a common therapy in a number of clinical settings. However, it is well understood that there is substantial donor‐to‐donor variation in how well PLTs store and thus the quality of the products that are transfused. The basis of such variation is poorly understood, and there are limited metrics by which units of PLTs can be assessed for their posttransfusion performance. It has repeatedly been demonstrated that myriad biologic changes take place during PLT storage; however, which of the changes correlate with quality of the stored PLTs and/or are mechanistically involved in PLT function remains undetermined. STUDY DESIGN AND METHODS: The current study tested stored PLTs from 21 normal subjects, combining high‐resolution metabolomics of stored PLTs with in vivo PLT recoveries and survivals. Both individual analytes and metabolic pathways that correlate with posttransfusion PLT viability were identified. RESULTS: Caffeine metabolites were associated with poor PLT recovery; caffeine metabolism was not ongoing in the PLT bag and remained at prestorage levels. Acylcarnitines, particular fatty acid metabolites, and oxidized fatty acids were associated with poor PLT survivals. Of the myriad metabolic changes during PLT storage, these are the first reported metabolic findings to begin distinguishing which changes are of functional importance regarding posttransfusion PLT performance. CONCLUSIONS: Together, these findings provide novel mechanistic insights into the functional biology of the PLT storage lesion as well as identifying potential targets for modifying donor environment (e.g., caffeine consumption) and also metrics of quality assessment for stored human PLTs.